Working on optical characterization setup for cutting-edge nanophotonics technology : part 2 - Lee, Xiao Yu (Nanyang Technological University, 2021)
Obtaining a highly efficient electrically excited (pump) light emitter material etched on Silicon has always been in the spotlight as the deciding factor for achieving monolithic photonic circuits. This would be a crucial breakthrough for both photonics and electronics. Over the years, Germanium (Ge) etched on Silicon (Si) has received a lot of attention due to its ability to be band engineered to achieve direct band gap properties. There has been successful implementation of Ge on Si on complementary metal oxide semiconductor (CMOS) and high performance photomodulators. However, research done so far has only been able to prove the lasing potential of Ge on Si at cryogenic temperatures and through mathematical proves. This is not optimal for the development of photonics circuits. The current works used various band engineering methods and incorporating band engineering methods together and using absorption as an indicator. There has not been a lot of research focusing on solely high tensile straining of the Ge on Si nanowire. As such, this project will be focusing on this gap, to study the relationship of Ge on Si through measuring transmission data. The transmission data collected are analyzed to observe optical gain (lasing) properties. In this fyp, I studied the effect of varying power on low strained and high strained Ge wire. To achieve this, pump probe measurement was used to find out about the optical properties and deduce meaningful transmission results that can be helpful in showing optical gain. From the findings of the data, the results proposed that at 2% strain at pump power higher than 300uW could be useful for optical gain observation for Ge on Si wire. This is because at 300uW there is a change in transmission value from negative to positive range, which is expected at material bleaching with stimulated emission thereafter.